Anti-ultraviolet eye protection paper containing lignocellulose nanofibers and preparation method of anti-ultraviolet eye protection paper

By using lignin cellulose nanofibers to prepare UV-proof eye protection paper, the problems of environmental toxicity and insufficient UV reflectivity in the existing technology are solved, efficient UV absorption and optical performance optimization are achieved, and the material is environmentally friendly and renewable.

CN120700738APending Publication Date: 2025-09-26TIANJIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511038466.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing anti-UV eye protection paper technology uses rare metal elements, which has environmental toxicity issues and insufficient optimization of UV reflectivity and optical performance.

Method used

Lignin cellulose nanofibers are used as coating liquid, and lignin cellulose nanofibers are prepared by sulfonation, electrostatic adsorption or TEMPO oxidation, and combined with functional additives to prepare UV-proof eye protection paper.

Benefits of technology

It effectively reduces ultraviolet reflectivity, reduces damage to human eyes, and improves ultraviolet and blue light absorption capacity, while maintaining the whiteness and reading comfort of the paper. The material is environmentally friendly and renewable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120700738A_ABST
    Figure CN120700738A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lignin application, and particularly relates to anti-ultraviolet eye protection paper containing lignocellulose nanofibers and a preparation method of the anti-ultraviolet eye protection paper. The anti-ultraviolet eye protection paper comprises raw paper and coating liquid coated on the surface of the raw paper, the coating liquid comprises lignocellulose nanofibers and a functional additive. Lignin serves as a natural high-molecular polymer which is the second rich in reserves in the nature, phenylpropane in the lignin contains conjugated double bonds and phenolic hydroxyl groups and can absorb ultraviolet light and part of blue light, and lignin and cellulose are natural renewable materials and are non-toxic and biodegradable. Lignin replaces a traditional chemical ultraviolet absorbent, and the problem of environmental toxicity is solved. And the lignin is added, so that better protection and absorption effects can be achieved in an ultraviolet region, and human eye injury is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lignin application, and particularly relates to an anti-ultraviolet eye protection paper containing lignin cellulose nanofibers and a preparation method thereof. Background Art

[0002] Ultraviolet rays can damage the eyes, entering from the outside and causing more or less damage to the conjunctiva, cornea, lens, etc., especially if not paid attention to for a long time. In severe cases, it can easily cause keratitis, macular degeneration, etc. The damage caused by ultraviolet rays to the eyes is hidden and irreversible. The core technology of current anti-ultraviolet eye protection paper is to reduce the reflectivity of ultraviolet rays through nanomaterial modification, while optimizing the optical performance of the human eye comfort band. For example, patent CN119800767A discloses a special eye protection paper and preparation method in which a mixture of nano-titanium dioxide and nano-zinc oxide is coated on the surface of paper; patent CN119243514A discloses a method in which nano-cerium oxide, nano-zinc oxide, inorganic nano-blue light absorber, nano-aluminum oxide, etc. are coated on the surface of paper, but the above patents use rare metal elements. Summary of the Invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an anti-ultraviolet eye protection paper containing lignin cellulose nanofibers and a preparation method thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is: Disclosed is an anti-ultraviolet eye-protection paper containing lignin cellulose nanofibers, comprising base paper and a coating liquid coated on the surface of the base paper; the coating liquid comprises lignin cellulose nanofibers and functional additives.

[0005] The lignin cellulose nanofibers are one of sulfonated lignin cellulose nanofibers, electrostatically adsorbed lignin cellulose nanofibers, TEMPO-oxidized lignin cellulose nanofibers or bleached lignin cellulose nanofibers, or a mixture thereof.

[0006] Preferably, the lignin content in the sulfonated lignin cellulose nanofibers is 27±2%; Preferably, the lignin content in the electrostatically adsorbed lignin cellulose nanofibers is 50±5%.

[0007] Preferably, the lignin content in the TEMPO-oxidized lignin-containing cellulose nanofibers is 24±2%.

[0008] Preferably, the lignin content in the bleached lignin-containing cellulose nanofibers is 21±2%.

[0009] The sulfonated lignin nanofibers are prepared by the following method: a DES solution is added to a lignin-containing wood pulp and subjected to high-pressure homogenization to obtain the sulfonated lignin nanofibers; the mass ratio of the dry weight of the lignin-containing wood pulp to the DES solution is 1:(1-4), the high-pressure homogenization pressure is 60-150 MPa, and the homogenization is repeated 2-15 times; The DES solution is prepared by mixing urea and aminosulfonic acid in a mass ratio of 1:1, heating and reacting until the liquid is clear and transparent to obtain a DES solution; the reaction temperature is 80-100°C, and the reaction time is 20-60 minutes, preferably 90°C for 30 minutes.

[0010] The electrostatically adsorbed lignin cellulose nanofibers are prepared by mechanically grinding alkali lignin and adding water to form a lignin suspension. The suspension is then subjected to two high-pressure homogenization steps at a pressure of 60-150 MPa. A cationic polymer is added at an amount of 1-40% of the dry weight of the lignin, preferably 10%. After uniform mixing, the suspension is subjected to high-pressure homogenization to obtain a cationic nano-lignin suspension. TOCNF is added to a cationic nano-lignin suspension for high-pressure homogenization to obtain electrostatically adsorbed lignin cellulose nanofibers, wherein the dry weight ratio of TOCNF to cationic nano-lignin is 1:(0.1-1); the high-pressure homogenization pressure is 60-150 MP, and the homogenization is performed 2-15 times.

[0011] The TEMPO-oxidized lignin-containing cellulose nanofibers are prepared by the following method: adding 2,2,6,6-tetramethylpiperidine-1-oxide TEMPO as a catalyst to wood pulp, simultaneously adding sodium bromide NaBr as a co-catalyst, adding NaOH to adjust the pH value to between 10 and 10.5, and adding sodium hypochlorite NaClO as an oxidant, and reacting at 20-25° C. for 2-4 hours; after the reaction is completed, washing with deionized water until neutral to obtain TEMPO-oxidized lignin-containing cellulose nanofibers; preferably, the amount of NaClO added is 8-16 mmol / g relative to the absolute dry weight of the wood pulp.

[0012] The bleached lignin-containing cellulose nanofibers are prepared by the following method: TEMPO-oxidized lignin-containing cellulose nanofibers are added to deionized water to adjust the concentration to 10-30%, heated to 80-110°C, and NaOH and Na2SiO3 are added; after kneading for 5-15 minutes, H2O2 is added, and H2O2 is added after reaction for 1-2 hours. After reaction for 3-4 hours, deionized water is added and washed until neutral.

[0013] The functional additive is one of polyvinyl alcohol (PVA), methyl cellulose, carboxymethyl cellulose, starch, oxidized starch and carboxymethyl starch, or a mixture thereof.

[0014] The present invention also includes a method for preparing the UV-proof eye-protection paper containing lignin cellulose nanofibers, comprising the following steps: S1: adding a functional additive to water to prepare a 1-10 wt% solution, mixing with a stirrer, and standing to defoam for use; S2: adding lignin cellulose nanofibers to the functional additive solution, mixing, and stirring to obtain a coating liquid containing lignin cellulose nanofibers; S3: applying the coating liquid to base paper to obtain the UV-proof eye-protection paper containing lignin cellulose nanofibers; the loading amount of the solid content in the coating liquid on the base paper is 1-10 g / m 2 .

[0015] Compared with the prior art, the present invention has the following beneficial effects: Lignin is the second most abundant natural polymer. The phenylpropane in lignin contains conjugated double bonds and phenolic hydroxyl groups that absorb ultraviolet light and some blue light. Both lignin and cellulose are naturally renewable, non-toxic, and biodegradable. The technical solution of this application replaces traditional chemical UV absorbers in the coating solution with lignin, addressing environmental toxicity concerns. The addition of lignin provides enhanced protection and absorption in the UV region, reducing eye damage.

[0016] The electrostatic adsorption method, a preferred method for preparing lignin-containing cellulose nanofibers, is simple to operate and highly scalable. The electrostatic adsorption process allows for easy control of the amount of lignin added, enabling a controlled lignin content in the lignin-containing cellulose nanofibers. The sulfonation system for preparing lignin-containing cellulose nanofibers uses mild reaction conditions, resulting in high lignin retention and better compliance with green chemistry requirements. H2O2 bleaching of the lignin-containing cellulose nanofibers allows for excellent control of paper whiteness. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The reflectivity shielding diagram of sulfonated lignin cellulose nanofiber anti-UV eye protection paper and the UV reflectivity of commercially available eye protection paper and copy paper; Figure 2 The reflectivity shielding diagram of electrostatically adsorbed lignin cellulose nanofiber anti-UV eye protection paper and the UV reflectivity of commercially available eye protection paper and copy paper; Figure 3 The reflectivity shielding diagram of TEMPO-oxidized lignin cellulose nanofiber anti-UV eye protection paper and the UV reflectivity of commercially available eye protection paper and copy paper; Figure 4 The reflectivity shielding diagram of bleached lignin cellulose nanofiber anti-UV eye protection paper and the UV reflectivity of commercially available eye protection paper and copy paper. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and the best embodiments.

[0019] Some of the raw materials used in this application are provided below: Alkali lignin and softwood raw materials were purchased from Hunan Juntai New Materials Technology Co., Ltd. Urea, aminosulfonic acid, polyvinyl alcohol, polydipropyldimethylammonium chloride, NaBr, TEMPO reagent, NaOH, NaClO, H2O2, and Na2SiO3 were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. TEMPO-oxidized cellulose nanofibers (TOCNFs) from bleached softwood kraft pulp were provided by Tianjin Wood Elf Biotechnology Co., Ltd.

[0020] Example 1: Sulfonated lignin cellulose nanofibers Preparation of UV-proof eye protection paper containing lignin cellulose nanofibers.

[0021] 1. Preparation of DES solution: First weigh urea and aminosulfonic acid in a mass ratio of 1:1, pour into a slurry barrel and mix evenly, place in a 90℃ water bath, and react for 30 minutes until the liquid is clear and transparent to obtain DES solution.

[0022] 2. Preparation of sulfonated lignin-containing cellulose nanofibers: In this example, 200 g of absolutely dry coniferous wood shavings were taken and mechanically ground to obtain coniferous pulp. DES solution was added to the coniferous pulp. The ratio of coniferous pulp (dry weight) to DES was 1:1, 1:2, 1:3, and 1:4, respectively. The reaction was carried out for 6 hours with continuous stirring during the reaction. After the reaction, the mixture was washed with deionized water until neutral. The addition amount of 1:1 corresponded to the obtained cellulose nanofibers with a lignin content of 27.75%, the addition amount of 1:2 corresponded to the obtained cellulose nanofibers with a lignin content of 27.37%, the addition amount of 1:3 corresponded to the obtained cellulose nanofibers with a lignin content of 27.13%, and the addition amount of 1:4 corresponded to the obtained cellulose nanofibers with a lignin content of 26.91%.

[0023] Cellulose nanofibers containing sulfonated lignin with lignin contents of 27.75%, 27.37%, 27.13%, and 26.91% were prepared into a slurry with a concentration of 1.1% using deionized water, and homogenized six times under a pressure of 100 MPa to obtain lignin cellulose nanofibers.

[0024] 3. Preparation of UV-proof eye protection paper: 40 g of polyvinyl alcohol (PVA) was prepared into a 5 wt% solution, and cellulose nanofibers of sulfonated lignin prepared by the sulfonation system (wherein the lignin contents were 27.57%, 27.37%, 27.13%, 26.91%, respectively, and the solid content was 1%).

[0025] The lignin cellulose nanofibers and polyvinyl alcohol were uniformly dispersed in 200 g of 5% PVA solution at a dry weight ratio of 1:1 using a high-speed disperser to prepare a lignin cellulose nanofiber coating solution. The lignin cellulose nanofiber coating solution was coated on the base paper using a rod coating method at a coating amount of 4 g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.

[0026] Comparative Example 1: uncoated base paper; Comparative Example 2: The preparation process of Comparative Example 2 is the same as that of Example 1, except that bleached softwood pulp is used instead of softwood shavings to obtain carboxyl-modified nanocellulose containing almost no lignin. The coating method is the same as that of Example 1.

[0027] Comparative Example 3: Four commercially available eye protection paper products (eye protection paper A, eye protection paper B, eye protection paper C, eye protection paper D), and commercially available copy paper E.

[0028] Figure 1 (a) shows a comparison of the reflectance curves of the paper product produced in Example 1 of the present invention across the entire UV-visible light band of 200-800nm. In the UV region (200-400nm), the UV-protective eye-protective paper produced in Example 1 with lignin contents of 27.57%, 27.37%, 27.13%, and 26.91%, respectively, exhibits average UV reflectances of 17.86%, 19.53%, 20.45%, and 24.51%. The average UV reflectances of Comparative Example 1 and Comparative Example 2 are 36.45%, and 37.47%. The UV-protective eye-protective paper in Example 1 significantly reduces reflectance against eye-damaging light in the UV region (200-400nm) and the harmful blue-violet region (400-480nm), while slightly increasing reflectance within the comfortable reading wavelength of 500-700nm. Furthermore, the reflectance increases slightly with a slight decrease in lignin content. When the uncoated base paper in Comparative Example 1 and the coating liquid in Comparative Example 2 do not contain lignin, they do not have the anti-ultraviolet function.

[0029] Figure 1(b) shows a comparison of the reflectance curves for Example 1 (lignin content of 27.57%) and Comparative Example 3 (four commercially available eye-protection paper products A, B, C, and D, and a commercially available copy paper E) across the full UV-visible range of 200 to 800 nm. In the UV region (200-400 nm), the average UV reflectances of the four commercially available eye-protection paper products A, B, C, and D in Comparative Example 3 were 17.48%, 22.94%, 39.99%, and 38.48%, respectively, while the average UV reflectance of commercially available copy paper E was 85.73%. In the UV region, the reflectance of Example 1's UV-resistant eye-protection paper was lower than that of commercially available eye-protection paper B, C, and D, and only 0.38% higher than the average reflectance of commercially available eye-protection paper A. Its eye-protection effect was superior to that of most commercially available paper products. This demonstrates that the UV-resistant eye-protection paper produced by the present invention can reduce reflectance in the UV region.

[0030] Table 1 shows the whiteness, fluorescent whiteness, and whiteness after 6 hours of irradiation under 300W, 360-365nm UV lamp irradiation for the UV-protective eye-protective paper produced in Example 1. Table 2 shows the whiteness, fluorescent whiteness, and whiteness after 6 hours of irradiation under 300W, 360-365nm UV lamp irradiation for the papers produced in Comparative Examples 1, 2, and 3 (A, B, C, D, and E). A comparison with Table 2 shows that the whiteness of the paper in Example 1 is approximately 10% lower than that of Comparative Examples 1 and 2, but still higher than that of the commercial eye-protective paper B in Comparative Example 3. The fluorescent whiteness is less than 0.2, and the whiteness is somewhat maintained after aging under high-intensity UV lamp irradiation, with a similar decrease as in the comparative example. Therefore, the UV-protective eye-protective paper produced in Example 1 is superior to the commercial eye-protective paper B in terms of whiteness.

[0031] Table 1

[0032] Table 2

[0033] Example 2: Preparation of UV-proof eye protection paper containing lignin cellulose nanofibers by electrostatic adsorption of lignin cellulose nanofibers.

[0034] 1. Preparation of electrostatically adsorbed lignin cellulose nanofibers: In this example, alkali lignin was mechanically ground and passed through a 200-mesh screen to obtain an alkali lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at a pressure of 60 MPa. A cationic polymer, polydipropyldimethylammonium chloride, was added in an amount equivalent to 10% of the dry weight of the lignin. After mixing, the suspension was homogenized 10 times at a pressure of 100 MPa to obtain a cationic nano-lignin suspension.

[0035] TOCNF (TEMPO system oxidized cellulose nanofiber, commercially available) was added to the cationic nanolignin suspension and mixed evenly. The absolute dry weight ratio of TOCNF to cationic nanolignin was 1:0.1, 1:0.2, 1:0.3, 1:0.5, and 1:1, respectively. Homogenization was performed twice under a pressure of 60 MPa to obtain electrostatically adsorbed lignin cellulose nanofibers.

[0036] 2. Preparation of UV-proof eye protection paper: 50g of polyvinyl alcohol (PVA) was prepared into a 5wt% solution and electrostatically adsorbed lignin cellulose nanofibers; The lignin cellulose nanofibers were uniformly dispersed into 200 g of 5% PVA solution at a mass ratio of 1:1 using a high-speed disperser to prepare a lignin cellulose nanofiber coating solution. The lignin cellulose nanofiber coating solution was then coated on paper using a rod coater at a coating amount of 4 g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.

[0037] Figure 2 (a) shows a comparison of the reflectance curves of the paper product produced in Example 2 of the present invention over the entire UV-visible light band of 200-800nm. In the UV region (200-400nm), the average UV reflectance of the UV-protective eye-protection paper produced in Example 2 with TOCNF to lignin absolute dry weight ratios of 1:0.1, 1:0.2, 1:0.3, 1:0.5, and 1:1, respectively, was 22.64%, 14.60%, 13.60%, 11.97%, and 5.61%. The UV-protective eye-protection paper in Example 2 significantly reduced its reflectance for eye-damaging light in the UV region (200-400nm) and the harmful blue-violet region (primarily 400-480nm). The reflectance decreased with increasing lignin addition, reaching a minimum average UV reflectance of 5.61% at a 1:1 addition ratio, demonstrating optimal UV protection.

[0038] Figure 2 Panel (b) compares the reflectance curves of Example 2 (selected for best performance) and Comparative Example 3 (four commercially available eye-protection paper products, A, B, C, and D, and a commercially available copy paper, E) across the full UV-visible range of 200-800 nm. In the UV region, the reflectance of Example 2 is lower than that of commercially available eye-protection papers A, B, C, and D, and its eye-protection effect is superior to that of all the commercially available paper products in the comparative examples. Therefore, the UV-protective eye-protection paper produced by the present invention can reduce reflectance in the UV region.

[0039] Table 3 shows the whiteness, fluorescent whiteness, and whiteness of the UV-blocking eye-protection paper produced in Example 2 after 6 hours of irradiation under a 300W, 360-365nm UV lamp. A comparison with Table 2 shows that the whiteness of the paper in Example 2 decreases significantly compared to all the comparative examples, with a fluorescent whiteness below 0.1. Furthermore, the whiteness is somewhat maintained after aging under high-intensity UV lamp irradiation.

[0040] Table 3

[0041] Example 3: TEMPO oxidation of lignin-containing cellulose nanofibers to prepare UV-proof eye protection paper containing lignin-containing cellulose nanofibers.

[0042] 1. Preparation of TEMPO-oxidized lignin-containing cellulose nanofibers: In this example, 200 g of absolutely dry softwood shavings were taken and mechanically refined to obtain softwood pulp. First, 8.5 L of deionized water and 24 g of NaBr were accurately weighed and poured into a pulp barrel. After stirring evenly, 4 g of TEMPO was added, and 0.5 M NaOH was used to adjust the pH to between 10.0 and 10.5. NaClO solution (8% effective chlorine content) was added. The addition amount was 8 mmol / g, 12 mmol / g, and 16 mmol / g relative to the softwood pulp, respectively, and the reaction time was 70 min. After the reaction was completed, deionized water was used to wash until neutral. Among them, 8 mmol / g corresponds to TEMPO-oxidized lignin-containing cellulose nanofibers with a lignin content of 24.51%, 12 mmol / g corresponds to TEMPO-oxidized lignin-containing cellulose nanofibers with a lignin content of 21.35%, and 16 mmol / g corresponds to TEMPO-oxidized lignin-containing cellulose nanofibers with a lignin content of 19.07%.

[0043] TEMPO-oxidized lignin-containing cellulose nanofibers with lignin contents of 24.51%, 21.35%, and 19.07% were prepared into a slurry with a concentration of 1.1% using deionized water, and homogenized 6 times under a pressure of 100 MPa to obtain lignin cellulose nanofibers.

[0044] 2. Preparation of UV-proof eye protection paper: 30 g of polyvinyl alcohol (PVA) was prepared into a 5 wt% solution, and TEMPO-oxidized lignin-containing cellulose nanofibers (solid content of 1%) were prepared.

[0045] The lignin cellulose nanofibers were uniformly dispersed into 200 g of 5% PVA solution at an absolute dry ratio of 1:1 using a high-speed disperser to prepare a lignin cellulose nanofiber coating solution. The lignin cellulose nanofiber coating solution was then coated on paper using a rod coater at a coating amount of 4 g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.

[0046] Figure 3 (a) shows a comparison of the reflectance curves for Example 3 of the present invention and Comparative Examples 1 and 2 over the full UV-visible range of 200-800 nm. In the ultraviolet region (200-400 nm), the UV-blocking eye protection paper produced in Example 1 with lignin contents of 24.51%, 21.35%, and 19.07%, respectively, had average UV reflectivities of 19.46%, 19.75%, and 21.53%. The average UV reflectivity for Comparative Example 1 was 36.45%, and for Comparative Example 2 was 37.47%. The results demonstrate that carboxyl-modified lignin-containing cellulose nanofibers can reduce UV reflectivity, with higher lignin content resulting in better UV-blocking performance.

[0047] Figure 3 Panel (b) compares the reflectance curves of Example 3 (selected for the best performance) of the present invention and Comparative Example 3 (four commercially available eye-protection paper products, A, B, C, and D, and a commercially available copy paper, E) across the full UV-visible range of 200 to 800 nm. The UV-resistant eye-protection paper produced by TEMPO-oxidizing lignin-containing cellulose nanofibers in the UV region has a lower reflectance than commercially available eye-protection papers B, C, and D, and exhibits superior UV light suppression to other paper products. Therefore, the UV-resistant eye-protection paper produced by the present invention can reduce UV reflectance while ensuring reading comfort, outperforming most commercially available paper products.

[0048] Table 4 shows the whiteness, fluorescent whiteness, and whiteness after 6 hours of aging under 300W, 360-365nm UV light for the UV-protective eye-protection paper produced in Example 3. It can be seen that the whiteness of the paper in Example 3 is lower than that of Comparative Examples 1 and 2, but still higher than that of the commercially available eye-protection papers A and B in Comparative Example 3. The fluorescent whiteness is lower than 0.1, lower than that of all the comparative examples. Furthermore, after aging under high-intensity UV light, the whiteness is somewhat maintained, with a similar degree of decline as in the comparative examples. Therefore, the UV-protective eye-protection paper produced in Example 3 is superior to the commercially available eye-protection papers A and B in terms of whiteness, and has a lower fluorescent whiteness, surpassing most commercially available paper products.

[0049] Table 4

[0050] Example 4: Bleaching of lignin-containing cellulose nanofibers to prepare UV-proof eye protection paper containing lignin-containing cellulose nanofibers.

[0051] 1. Preparation of bleached lignin-containing cellulose nanofibers: In this example, the TEMPO-oxidized lignin-containing cellulose nanofibers in Example 3 were adjusted to a concentration of 20% with deionized water, loaded into a reactor equipped with a stirring device, and the temperature was adjusted to 95°C. After preheating for 10 minutes, 3% by mass (relative to the TEMPO-oxidized lignin-containing cellulose nanofiber mixture, the same below) of NaOH and 1% by mass of Na2SiO3 were added, respectively. After kneading for 10 minutes, 5% by mass of H2O2 was added. After reacting for 2 hours, 3% by mass of H2O2 was added. The mixture was reacted for a total of 3 hours and then washed with deionized water until neutral, obtaining bleached lignin cellulose nanofibers with lignin contents of 21.77%, 19.55%, and 17.02%.

[0052] Bleached lignin-containing cellulose nanofibers with lignin contents of 21.77%, 19.55%, and 17.02% were prepared into a slurry with a concentration of 1.1% using deionized water, and homogenized six times under a pressure of 100 MPa to obtain lignin cellulose nanofibers.

[0053] 2. Preparation of UV-proof eye protection paper: 30 g of polyvinyl alcohol (PVA) was prepared into a 5 wt% solution and bleached lignin-containing cellulose nanofibers, and H2O2 bleached lignin cellulose nanofibers (solid content was 1%).

[0054] The lignin-containing cellulose nanofibers were uniformly dispersed into 200 g of 5% PVA solution at a mass ratio of 1:1 using a high-speed disperser to prepare a lignin-containing cellulose nanofiber coating solution. The prepared lignin-containing cellulose nanofiber coating solution was coated on paper using a rod coating method at a coating amount of 4 g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.

[0055] Figure 4 Figure (a) compares the reflectance curves of Example 4 and Comparative Example 1 across the full UV-visible wavelength range of 200-800 nm. In the UV region (200-400 nm), the UV-protective eye protection paper produced in Example 4 with lignin contents of 21.77%, 19.55%, and 17.02%, respectively, exhibits average UV reflectances of 26.70%, 28.98%, and 30.75%. The UV absorption capacity of the bleached lignin-containing cellulose nanofibers in Example 4 is somewhat lower than that of 19.46% in Example 3 (selected for optimal performance), but still exhibits reasonable UV protection.

[0056] Figure 4Panel (b) compares the reflectance curves of Example 4 (selected for optimal performance) of the present invention and Comparative Example 3 (four commercially available eye protection paper products, A, B, C, and D, and commercial copy paper E) across the entire UV-visible range of 200-800 nm. In the UV region, the reflectance of Example 4 is lower than the 39.99% and 38.48% of commercially available eye protection papers C and D, respectively. Its reflectance is similar to that of commercially available eye protection paper B in the UVB (280-315 nm) and UVC (315-400 nm) regions, and its reflectance is slightly higher than that of eye protection paper B in the UVA (200-280 nm) region. Therefore, the UV-resistant eye protection paper produced by the present invention can reduce reflectance in the UV region.

[0057] Table 5 shows the whiteness, fluorescent whiteness, and whiteness after aging under 300W, 360-365nm UV lamp for 6 hours of the UV-protective eye-protection paper produced in Example 4. A comparison with Table 2 shows that the whiteness of the paper in Example 4 decreases by 1-2% compared to Comparative Examples 1 and 2, but is still higher than the commercially available eye-protection papers A, B, C, and D in Comparative Example 3. The fluorescent whiteness is less than 0.2, and the whiteness remains somewhat maintained after aging under high-intensity UV lamp irradiation, with a similar decrease as in the comparative examples. Therefore, the UV-protective eye-protection paper produced in Example 4 is superior to the commercially available eye-protection papers A, B, C, and D in whiteness, and is more effective than commercially available eye-protection paper products.

[0058] Table 5

[0059] In summary, the electrostatic adsorption method for preparing lignin-containing cellulose nanofibers is simple to operate and highly scalable. The electrostatic adsorption process allows for easy control of the amount of lignin added, resulting in a controllable lignin content. The sulfonation system for preparing lignin-containing cellulose nanofibers offers mild reaction conditions and high lignin retention, further meeting the requirements of green chemistry. H₂O₂ bleaching of the lignin-containing cellulose nanofibers allows for excellent control of paper whiteness.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. An anti-ultraviolet eye protection paper containing lignin cellulose nanofibers, characterized in that: The invention comprises base paper and a coating liquid coated on the surface of the base paper; the coating liquid comprises lignin cellulose nanofibers and functional additives.

2. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 1, characterized in that: The lignin cellulose nanofibers are one of sulfonated lignin cellulose nanofibers, electrostatically adsorbed lignin cellulose nanofibers, TEMPO-oxidized lignin cellulose nanofibers or bleached lignin cellulose nanofibers, or a mixture thereof.

3. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 1, characterized in that: The lignin content in the sulfonated lignin cellulose nanofibers is 27±2%; The lignin content in the electrostatically adsorbed lignin cellulose nanofibers was 50 ± 5%; The lignin content in TEMPO-oxidized lignin-cellulose nanofibers was 24 ± 2%; The lignin content in the bleached lignin cellulose nanofibers was 21±2%.

4. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 2, characterized in that: The sulfonated lignin nanofibers are prepared by the following method: a DES solution is added to a lignin-containing wood pulp and subjected to high-pressure homogenization to obtain the sulfonated lignin nanofibers; the mass ratio of the dry weight of the lignin-containing wood pulp to the DES solution is 1:(1-4), the high-pressure homogenization pressure is 60-150 MPa, and the homogenization is repeated 2-15 times; The DES solution is prepared by uniformly mixing urea and aminosulfonic acid in a mass ratio of 1:1, heating and reacting until the liquid becomes clear and transparent to obtain the DES solution; the reaction temperature is 80-100°C, and the reaction time is 20-60 minutes.

5. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 2, characterized in that: The electrostatically adsorbed lignin cellulose nanofibers are prepared by mechanically grinding alkali lignin and adding water to form a lignin suspension. The suspension is then subjected to two high-pressure homogenization steps at a pressure of 60-150 MPa. A cationic polymer is added at an amount of 1-40% of the dry weight of the lignin. The mixture is then uniformly mixed and then subjected to high-pressure homogenization to obtain a cationic nano-lignin suspension. TOCNF is added to a cationic nano-lignin suspension for high-pressure homogenization to obtain electrostatically adsorbed lignin cellulose nanofibers, wherein the dry weight ratio of TOCNF to cationic nano-lignin is 1:(0.1-1); the high-pressure homogenization pressure is 60-150 MP, and the homogenization is performed 2-15 times.

6. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 2, characterized in that: The TEMPO-oxidized lignin-containing cellulose nanofibers are prepared by the following method: adding 2,2,6,6-tetramethylpiperidine-1-oxide (TEMPO) as a catalyst to wood pulp, simultaneously adding sodium bromide (NaBr) as a co-catalyst, adding NaOH to adjust the pH value to between 10 and 10.5, and dropwise adding sodium hypochlorite (NaClO) as an oxidant. The reaction is carried out at 20-25° C. for 2-4 hours. After the reaction is completed, the TEMPO-oxidized lignin-containing cellulose nanofibers are washed with deionized water until neutral, thereby obtaining the TEMPO-oxidized lignin-containing cellulose nanofibers. The amount of NaClO added is 8-16 mmol / g relative to the absolute dry weight of the wood pulp.

7. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 6, characterized in that: The bleached lignin cellulose nanofibers are prepared by the following method: TEMPO-oxidized lignin cellulose nanofibers are added to deionized water to adjust the concentration to 10-30%, heated to 80-110°C, and NaOH and Na2SiO3 are added; after kneading for 5-15 minutes, H2O2 is added, and H2O2 is added after reaction for 1-2 hours. After the total reaction time of 3-4 hours, deionized water is added and washed until neutral to obtain the bleached lignin cellulose nanofibers.

8. The UV-proof eye-protection paper containing lignin cellulose nanofibers according to claim 1, characterized in that: The functional additive is one of polyvinyl alcohol (PVA), methyl cellulose, carboxymethyl cellulose, starch, oxidized starch and carboxymethyl starch, or a mixture thereof.

9. A method for preparing the UV-proof eye-protection paper containing lignin cellulose nanofibers according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: S1: adding a functional additive to water to prepare a 1-10 wt% solution, mixing with a stirrer, and standing to defoam for use; S2: adding lignin cellulose nanofibers to the functional additive solution, mixing, and stirring to obtain a lignin cellulose nanofiber coating solution; S3: Apply the coating liquid to the base paper to obtain the UV-proof eye-protection paper containing lignin cellulose nanofibers; the loading amount of the solid content in the coating liquid on the base paper is 1-10g / m 2 .

Citation Information

Patent Citations

  • Anti-reflection eye protection functional paper and preparation method thereof

    CN119243514A

  • Special eye protection paper and preparation method thereof

    CN119800767A